2006
DOI: 10.1128/jcm.00330-06
|View full text |Cite
|
Sign up to set email alerts
|

Mutations Prevalent among Rifampin- and Isoniazid-Resistant Mycobacterium tuberculosis Isolates from a Hospital in Vietnam

Abstract: Vietnam is ranked 13th among the WHO list of 22 high-burden countries, based upon estimated total number of tuberculosis cases. Despite having a model national tuberculosis program, consistently achieving and exceeding WHO targets for detection and cure, drug-resistant and multidrug-resistant tuberculosis cases continue to rise. Rapid multidrug-resistant tests applicable in this setting, coupled with effective treatment regimens, would be a useful tool in reversing this trend, allowing early identification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
56
3
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 25 publications
18
56
3
1
Order By: Relevance
“…32 The most common missense mutations associated were located at codons 531 and 526. 8,33,34 However, some studies have also reported other uncommon mutations inside and outside of the "hot-spot" region that were regularly or even systematically missed by standard, World Health Organization-endorsed DST methods. 35,36 The most sensitive limit of detection theoretically possible is three copies per PCR reaction, assuming a Poisson distribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 The most common missense mutations associated were located at codons 531 and 526. 8,33,34 However, some studies have also reported other uncommon mutations inside and outside of the "hot-spot" region that were regularly or even systematically missed by standard, World Health Organization-endorsed DST methods. 35,36 The most sensitive limit of detection theoretically possible is three copies per PCR reaction, assuming a Poisson distribution.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Rifampicin (R), resistance is mostly (96%) due to mutations in an 81-(base pair) bp "hot-spot" region of the rpoB gene that encodes the β-subunit of RNA polymerase, especially in codons 531 (43-56%) and 526 (8-31%). [7][8][9][10] Several molecular methods are available for detection of drug resistance mutations, including denaturing gradient gel electrophoresis, conformation-sensitive gel electrophoresis, temperature gradient capillary electrophoresis, denaturing highperformance liquid chromatography, high-density oligonucleotide arrays, and high-resolution melting analysis. [11][12][13][14][15][16][17] These methods vary in sensitivity and are either labor intensive, require sophisticated equipment to perform analyses, or present ambiguity in interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…A test screening for katG_315 mutations is likely to be of the most use in regions with a high prevalence of this mutation, such as China, Russia, the former Soviet states, Vietnam, and Peru (3,5). In Europe, a higher prevalence of inhA gene mutations indicates that a multiplex PCR or hybridization approach is warranted (2,4,19).…”
Section: Discussionmentioning
confidence: 99%
“…Previous sequencing data on isoniazid-resistant isolates from Vietnam indicated that around 80% of isoniazid-resistant isolates could be detected through katG_315 analysis, with katG_S315T being by far the most prevalent mutation (71%) (3). A restriction enzyme test specific for digestion of the CMGCKG site, found at wild-type katG_315, was therefore developed.…”
mentioning
confidence: 99%
“…4,5 Beberapa penelitian menyatakan lebih dari 90% penderita TB yang resisten rifampisin, juga mengalami resistensi terhadap isoniazid, sehingga resistensi terhadap rifampisin merupakan penanda pengganti (surrogate marker) yang mewakili suatu MDR-TB. [6][7][8][9] Rifampisin bekerja dengan berikatan terhadap subunit-β ribonucleic acid (RNA) polimerase yang dikode oleh gen rpoB, suatu komponen penting dalam proses transkripsi. Terhambatnya transkripsi RNA ini menyebabkan terhambatnya sintesis protein.…”
Section: 2unclassified